Rancang Bangun Sistem Informasi E-Voting Pemilihan Ketua Osis SMK Negeri 4 Kabupaten Tangerang Berbasis Web dengan Metode Rapid Application Development - Ade Maulana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The manual, paper-based election of the Student Council President faces various challenges, such as the lengthy vote counting process and the potential for errors in the recapitulation. To address these issues, this study designed a web-based e-voting information system at SMK Negeri 4 Tangerang Regency. This system was built using the Rapid Application Development (RAD) method, which emphasizes speed of development through iteration and prototyping based on user feedback. The development results indicate that e-voting can accelerate voting and vote counting, provide real-time results, and reduce paper usage. This system has been tested using blackbox testing, proving that all functions work as expected and are easily accessible to students. The study concludes that the implementation of web-based e-voting can improve efficiency, security, and transparency in the election of the Student Council President, with suggestions for system usage simulations and regular usability evaluations. Furthermore, this study also shows that the implementation of a web-based e-voting system can reduce the potential for fraud that often occurs in manual elections. With an automated and integrated system, every vote cast by voters is recorded accurately, reducing human error in the vote counting process. System security is also maintained through authentication mechanisms that ensure only authorized users can vote, as well as data encryption to protect sensitive information. This increases voter confidence in the election results, as the process is more transparent and free from manipulation. Furthermore, although the e-voting system has proven effective in increasing election efficiency and accuracy, the study also recommends the need for training for system users, both students and election committee members, to ensure they can utilize the system optimally. Continuous evaluation of the system's usability is also crucial to ensure that the interface remains user-friendly and easily accessible to all parties.